2013
DOI: 10.7731/kifse.2013.27.4.61
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of ROSC for Out-of Hospital Cardiopulmonary Resuscitation: Based on one Area Heart Saver

Abstract: This study was to investigate the cardiopulmonary resuscitation (CPR) outcomes and the clinical characteristics of outof-hospital cardiac arrest (OHCA) by analyzing date in one region. A total 8 patients, survived over 72 hours after ROSC. The cardiac arrest were caused by unknown (5 cases), cardiac disease (3 cases). The most common place of cardiac arrest was in the home (6 cases), witnessed cardiac arrest (8 cases), cardiopulmonary resuscitation by bystander was performed (4 cases), agonal respiration (3 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Roh et al reported that two dispatchers accounted for 12.5% and 3 dispatchers accounted for 87.5%. [4]. Lee reported that two dispatchers accounted for 89.9%(Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Roh et al reported that two dispatchers accounted for 12.5% and 3 dispatchers accounted for 87.5%. [4]. Lee reported that two dispatchers accounted for 89.9%(Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The another problem of chest compression is complication. Although the appropriate chest compression, it can develop rib and sternal fracture and cardiac and pulmonary contusion [4,5]. At least 5 to 10 minutes CPR must be performed before transport.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, manikin feedback can contribute to enhancing the quality of basic CPR at the scene. To increase the return of spontaneous circulation (ROSC) with OHCA patients, continuous basic CPR education programs are needed along with effective training (20) . It is also necessary to study the effect of music and metronome practice after VSI on CPR retention.…”
Section: Discussionmentioning
confidence: 99%